Analysing South African law on animal rights and the prosecution of animal cruelty - Pretorius, Claudia Jessica (The IIE, 2022)
Cruelty towards animals have become an increasing concern in the last few years as numbers of animal cruelty and neglect have been rising. The law affords rights that protect animals against mistreatment and harm caused by both humans and environmental conditions. Legislation plays a vital role in ensuring that the welfare of animals is guaranteed. The two questions that arise here are whether South African legislation provides for the protection and wellbeing of animals and whether these rights are effectively enforced. The prosecution of animal cruelty is another crucial function of the law, along with the effective implementation of rights. Statistics of cruelty provides insight on the whether there has been an increase or decrease in recent animal cruelty cases. A recent statistic shows an average of 249 animal cruelty cases a month in South Africa.1 This indicates a very high number of cases which does not include cases of animal abuse that are not being reported. Not only have cats and dogs been subjected to abuse but the welfare of farm animals and animals held in captivity for the attraction of tourism have been scrutinised. The current conditions of animal welfare have become a concern for organisations such as the SPCA2 and the Animal Anti-Cruelty League (hereinafter referred to as AACL).
Keywords: South African; Animal rights; Prosecution; Animal cruelty